Smart Urban Forest Management in East Africa: The Case of Nairobi and Kampala Cities - Sylvester Ngome Chisika; Chunho Yeom (SAGE Open, 2023)
Digital technologies are increasingly being incorporated in the management and governance of urban forests to provide the information needed for sustainable and more livable cities. However, there is scarce information on the documented lessons from applying these digital technologies for urban forestry management in many developing countries. This study addressed this challenge using a literature review in the case of Nairobi, Kenya, and Kampala, Uganda. The results substantiate that urban forests are important city assets enhancing ecological stability and sustainable development. As such, the digital technologies of urban forest management practices are rapidly expanding in the two cities to enhance urban forestry and create new opportunities for sustainable development. Both cities have differentiated integration of digital technologies in the vegetative, community support, and resource management components of urban forest governance and management, with important information and lessons being generated for city authorities and policymakers. In general, the technology implementation level in Kampala city is higher than in Nairobi City. This differentiation could be attributed to differences in the socio-political contexts of the two cities, which present different enablers and barriers to technology application in urban forestry. Nevertheless, more location-specific practices and experiences with a focus on how to diversify opinions and actors in digital technologies should be pursued.